Architecture of the active post‐translational Sec translocon. (11th December 2020) - Weng, Tsai‐Hsuan; Steinchen, Wieland; Beatrix, Birgitta; Berninghausen, Otto; Becker, Thomas; Bange, Gert; Cheng, Jingdong; Beckmann, Roland
Abstract: In eukaryotes, most secretory and membrane proteins are targeted by an N‐terminal signal sequence to the endoplasmic reticulum, where the trimeric Sec61 complex serves as protein‐conducting channel (PCC). In the post‐translational mode, fully synthesized proteins are recognized by a specialized channel additionally containing the Sec62, Sec63, Sec71, and Sec72 subunits. Recent structures of this Sec complex in the idle state revealed the overall architecture in a pre‐opened state. Here, we present a cryo‐EM structure of the yeast Sec complex bound to a substrate, and a crystal structure of the Sec62 cytosolic domain. The signal sequence is inserted into the lateral gate of Sec61α similar to previous structures, yet, with the gate adopting an even more open conformation. The signal sequence is flanked by two Sec62 transmembrane helices, the cytoplasmic N‐terminal domain of Sec62 is more rigidly positioned, and the plug domain is relocated. We crystallized the Sec62 domain and mapped its interaction with the C‐terminus of Sec63. Together, we obtained a near‐complete and integrated model of the active Sec complex. SYNOPSIS: The overall architecture of the eukaryotic SecY/Sec61 channel for post‐translational protein translocation, and how it recognizes N‐terminal signal sequences in transported proteins, remain unclear. Here, structural analyses reveal the molecular architecture of the engaged yeast Sec complex, which binds the signal sequence in a unique open conformation. Cryo‐EM structures of the heptameric Sec complex reveal the conformational transition from the partially open apo‐state to the fully open signal sequence‐bound state. The signal sequence binds the lateral gate of the Sec61 complex, which is stabilized by the transmembrane helices of the Sec62 subunit. The X‐ray structure of the N‐terminal cytoplasmic domain of Sec62 reveals a novel fold that is coordinated by the phosphorylated C‐terminal peptide of the Sec63 subunit. Abstract : Cryo‐electron microscopy and X‐ray crystallography studies reveal the molecular architecture of the engaged eukaryotic heptameric Sec complex, binding the protein signal sequence in an open conformation.